Integrating Digital Tools for Health Professional Education: A Case Study from the University of Peradeniya - H.M. Sandali Sathma Illangakoon; K.S.H.M.V.W. Walter Senevirathne (Talenta Publisher, 2026)
Background: The integration of digital tools into medical education has accelerated in recent years, but their effective use remains uneven across contexts. Objective: To examine usage patterns, student perceptions, and challenges related to digital learning tools among undergraduate medical students at the University of Peradeniya. Methods: A mixed-method case study design was used. Quantitative data from a structured Google Form survey (n = 100) provided numerical trends on tool usage and perceived effectiveness. Qualitative data from informal interviews were analysed thematically to explain and elaborate on the survey findings. The two datasets were integrated during interpretation, where qualitative insights were used to clarify and contextualise the quantitative results. Results: Findings showed that while tools like Moodle, Zoom, WhatsApp, and YouTube are widely used, student engagement was mostly passive. Only a minority used interactive tools such as online quizzes or gamified apps. Over 70% of students reported that digital tools support their understanding and engagement. Major challenges included poor internet access, lack of awareness, and minimal faculty support. Conclusion: Although digital tools are common, their pedagogical potential remains underutilized. Improved infrastructure, awareness, and integration are needed to optimize their impact in medical education.